HUBUNGAN PERSEPSI WISATAWAN TERHADAP SAMPAH DI PANTAI NAMALATU DESA LATUHALAT KECAMATAN NUSANIWE KOTA AMBON - Meyer, Julyan; Leiwakabessy, Fredy; Smith, Alwi (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2020)
Background: The tourists’ perception on Garbage at the tourism object in Namalatu beach. Garbage is threated in developing it. For that, the purpose of the research was to know the tourists’ perception on it. This aimed to know it in Namalatu beach, Ambon city Method: The type of the research used quantitative with analyze technic test correlation IBM statistics program version 22.0 for windows and the collected of data was questioner using ordinal scale on the tourist in Namalatu amount of 55 respondents Result: There were correlation on the tourists and garbage volume significant correlated (relation). The correlation coefficient was 0,846 empower both variable significant (P) rating 0.000 < 0, 05. Conclusion: with the correlation degree positive data means as the highest as the tourists’ perception as degree as satisfaction and comfortable on the tourism object in Namalatu beach which were clean and free on garbage.